On the body and the skin of the city: reading shame and violence through “programmatic marking” on the surfaces of Athens’ urban landscape - Kritikos, Christos-Georgios (Interdisciplinary applications of shame/violence theory, 2022)
This chapter examines James Gilligan’s shame/violence model as a tool for interpreting unauthorised marking of public space with the use of graffiti, tags, stencils etc. Based on recent literature that has highlighted the rich, multifaceted, performative aspects of the graffiti made by underground subcultures and/or mainstream street artists in modern Athens, we focus on a specific sub-category of graffiti, which we call “programmatic marking” on the surface of Athenian buildings. Programmatic marking is introduced to describe pre-planned, creative interventions, performed with the aim of communicating messages related to specific segments of the built environment, and to their history, identity, role, authority etc. in public space. In order to interpret this kind of urbicide, we follow Alessandra Lemma’s psychoanalytical conceptualisation of the various interventions on the human skin, as it helps us examine programmatic marking as an analogous violent intervention on the “skin” of the city. Under this perspective, Gilligan’s model and Lemma’s theoretical inquiry converge with Alison Young’s analyses of graffiti and street art practices as affective encounters, in order to link the biggest scale of the public realm to the smallest scale of bodily intimacy. The examination of selected case studies from the past decade illuminates different ways in which collective shame and/or pride has been expressed through unauthorised interventions in Athens’ public space.